Setting up a school library for Cherished Moments School - Bangsal, Raisa Faye A.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
The school library is considered to be effective and efficient part of the school that will help the students learn more about the world beyond their curriculum. It also advocates reading and learning as a whole for students and teachers alike. This study is aimed at creating a library plan with a collection development plan and policy, floor plan, etc. for the Cherished Moments School Library.
The study employed the descriptive and qualitative methods of research. The respondents were the students, faculty and staff. Interview with the librarian and the administration were conducted. The study seeks to find the user needs assessment and documentary analysis to see the present situation of the school and its users. The study revealed that the respondents see their library in complete disarray and needs more computer units as well as WiFi connection.The teachers see that there is a need for more space for the library to hold more students since the K-12 implementation to the school and the need for a library system for the library.They also seek to have a Teachers Corner. Upon interview with the administration, the need for more personnel is their priority but with other issues the school face such as the expansion of classrooms and the incoming Grade 12, the library is the least priority.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Cherished Moments School; School libraries